Conflict and the Composition of Economic Activity in Afghanistan - Galdo, Virgilio; Lopez-Acevedo, Gladys; Rama, Martin (World Bank, Washington, DC, 2020)
Despite informality being the norm in conflict-affected countries, most estimates of the impact of conflict on economic activity rely on formal sector data. Using high-frequency data from Afghanistan, this paper assesses how surges in conflict intensity affect not only the formal sector, but also informal and illicit activities. Nighttime light provides a proxy for aggregate economic activity, mobile phone traffic by registered firms captures fluctuations in formal sector output, and the land surface devoted to poppy cultivation gives a measure of illicit production. The unit of observation is the district and the period of reference is 2012-16. The same dynamic specification and controls are used for the estimation in the three cases, making the results comparable across sectors. Controls include the presence of combat troops and the level of foreign aid at the local level, which both influence local living standards in Afghanistan. The results show that an increase in conflict-related casualties has a strong negative impact on formal economic activity in the following quarter and a positive effect on illicit activity after two quarters. The impact on aggregate economic activity is negative, but more muted.